The Use of ICT for Assessment and Evaluation - Muhammad Naqeebul Khalil Shaheen (International Islamic University Islamabad, 2020)
Information and communication technology (ICT) has become an integral part of the education system round the globe. E-assessment and evaluation have gained the status of the most reliable emerging trends in information and communication technology to get a brief assessment of complex competencies. The major purpose of this study was to review the use of ICT for assessment and evaluation in the educational settings of Pakistan in terms of shifting from paper based assessment to e-assessment, opportunities and challenges for this shift and future inculcation of assessment and evaluation in the educational settings. The study concluded that there shifting from paper based assessment to e-assessment requires four generations i.e. e-assessment, adaptive tests, transforming assessment and automated scoring. The former two are practiced more frequently in the educational setting, while, there is a need to practice the latter two. Furthermore, a number of tools and settings undertaken to assess learners’ skills are not widely used in the field of education and still passing the experimental phase. The study recommends policy action for developing curriculum-fit ICT settings, knowledge exchange through teachers’ networking and providing guidance and encouragement for the use of ICT for Assessment and Evaluation.